Strong consistency of a deconvolution estimator of cumulative distribution function (Statistics, Optimization & Information Computing, 2023)
We study the strong consistency of a deconvolution estimator of cumulative distribution function when the distribution of error variable is assumed to be known exactly and ordinary smooth as well as supersmooth.